Maintenance Therapy Can Improve the Oncologic Prognosis and Obstetrical Outcome of Patients With Atypical Endometrial Hyperplasia and Endometrial Cancer After Fertility-Preserving Treatment: A Multicenter Retrospective Study - He, Yijiao; Wang, Jianliu; Wang, Yiqin; Zhou, Rong; Lu, Qun; Liu, Guoli; Tang, Huiru; Guo, Hongyan; He, Mian; Wu, Guizhu (Frontiers in Oncology, 2021)
Objective: To evaluate the effect of maintenance therapy for patients with atypical endometrial hyperplasia (AEH) and early endometrial cancer (EC) after successful fertility-preserving management on prognosis and pregnancy outcome. Methods: We performed a retrospectively analysis of 109 young women with atypical endometrial hyperplasia and early endometrioid endometrial cancer who had received complete response after fertility-preserving treatment at 5centers between May 2005 and March 2021. Maintenance therapy regimes included low-dose oral progesterone, levonorgestrel intrauterine device(LNG-IUD) and combination oral contraceptive (COC). The patients were divided into two groups, maintenance therapy group and non-maintenance therapy group. Clinical characteristics, treatment regimens, prognosis, and pregnancy outcome were compared between the two groups. Results: The overall disease recurrence rate of the maintenance therapy group was significantly lower than that of the non-maintenance therapy group (P < 0.001). The recurrence rate of atypical endometrial hyperplasia and endometrial cancer in the maintenance therapy group were significantly lower than those in the non-maintenance group (P < 0.001). Maintenance therapy can reduce pregnancy rates and live birth rates. Maintenance therapy can protect the endometrium in patients treated with assisted reproductive technology (ART), greatly reducing the recurrence rate after ART (P＜0.001). Conclusion: Maintenance therapy plays a very important protective role in fertility-preserving treatment for patients with atypical endometrial hyperplasia and endometrial cancer, which could significantly reduce the risk of recurrence. It is recommended that patients could receive maintenance therapy as long as possible during the period from achieving complete response to pregnancy preparation if possible. It may provide recurrence-free survival long enough for childless young women to prepare for pregnancy in the future. It can also protect the endometrium of those who are preparing to use assisted reproductive technology, possibly by reducing the risk of recurrence by excessive stimulation with assisted reproductive drugs.